NeuroThera® Efficacy and Safety Trial - 3 (NEST-3): a double-blind, randomized, sham-controlled, parallel group, multicenter, pivotal study to assess the safety and efficacy of transcranial laser therapy with the NeuroThera® laser system for the treatment of acute ischemic stroke within 24 h of stroke onset: - Zivin, Justin A.; Sehra, R.; Shoshoo, A.; Albers, G. W.; Bornstein, N. M.; Dahlof, B.; Kasner, S. E.; Howard, G.; Shuaib, A.; Streeter, J.; Richieri, S. P.; Hacke, Werner (International journal of stroke, 2014)
Rationale Transcranial laser therapy is undergoing clinical trials in patients with acute ischemic stroke. The NeuroThera® Efficacy and Safety Trial-1 was stron...
Published online27 September 2012
Gesehen am 21.07.2020